2018
DOI: 10.5424/sjar/2017154-11769
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: The main factors affecting somatic cell count in organic dairy farming

Abstract: Preventive management practices are essential for maintaining acceptable udder health status, especially in organic farming, in which the use of antimicrobials is restricted. The contribution of the following factors to somatic cell count (SCC) was assessed in 788 cows from 15 organically reared herds in northern Spain: milk production, lactation number, treatments applied, selective dry cow therapy and teat dipping routines. The data were examined by linear logistic regression. Lactation number was the main f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, our results are in agreement with studies conducted in Northern Spain, which showed higher SCC in ORG than CONV herds (Villar and López-Alonso, 2015;Orjales et al, 2016bOrjales et al, , 2017, partially associated with higher prevalence of chronic subclinical mastitis in ORG farms (Villar et al, 2016). The increase in SCC has been linked to increasing parity, with the use of alternative treatments instead of antibiotics, without use of teat dipping in the milking routine, and with lower milk production (Orjales et al, 2017). This last aspect was explained by a dilution effect related to greater milk production.…”
Section: Effects On Bulk Milk Gross Composition Scs Vite and Aa Compo...supporting
confidence: 93%
See 1 more Smart Citation
“…However, our results are in agreement with studies conducted in Northern Spain, which showed higher SCC in ORG than CONV herds (Villar and López-Alonso, 2015;Orjales et al, 2016bOrjales et al, , 2017, partially associated with higher prevalence of chronic subclinical mastitis in ORG farms (Villar et al, 2016). The increase in SCC has been linked to increasing parity, with the use of alternative treatments instead of antibiotics, without use of teat dipping in the milking routine, and with lower milk production (Orjales et al, 2017). This last aspect was explained by a dilution effect related to greater milk production.…”
Section: Effects On Bulk Milk Gross Composition Scs Vite and Aa Compo...supporting
confidence: 93%
“…This last aspect was explained by a dilution effect related to greater milk production. As discussed by Orjales et al (2017), ORG farms are usually low-input systems that lead to lower milk production levels compared with CONV farms. However, the dilution effect does not apply to our scenario, because our study included farms with a similar annual average milk production per cow (Table 1).…”
Section: Effects On Bulk Milk Gross Composition Scs Vite and Aa Compo...mentioning
confidence: 99%
“…As was expected, in the present study LS and percentage of SCC surpassing >200,000 somatic cells increased with lactation number in all breed groups (Reneau, ). These increases become more evident when cows survive during many lactations (Tancin, ) as in organic systems (Orjales Galdo et al, ; Orjales et al, ). Studies carried out in organic and pasture‐based systems to evaluate the effect of breed on SCC, LS or udder health produce inconclusive results, although only broad comparisons can be made.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, in most studies which reported significant differences in SCC, the levels were still below 400,000 cells per mL in both conventional and organic milk. At present, the employed farming system appears to have less influence on udder health compared with management factors (e.g., routine teat dipping and seeking veterinary treatment) and animal level variables (e.g., parity, breed) [36,[77][78][79]. Hence, making a generalization about whether organic farmers have a lower tolerance for poor udder health is not feasible due to potential variations in ethical considerations and divergent regulations regarding the use of antibiotics as a treatment option for organic cows among different countries [63].…”
Section: Udder Health and Somatic Cell Count (Scc)mentioning
confidence: 99%
“…Similar to milk SCCs, contradictory results have been reported regarding increased or decreased TBCs when comparing raw milk produced using organic and conventional systems [23]. Differing TBCs across studies have been attributed to management factors and animal-level variables [36,[77][78][79].…”
Section: Microbiological Qualitymentioning
confidence: 99%